Comparative transcriptome analysis and phenotypic monitoring of Trifolium pratense (Fabaceae) under land use scenarios - Herbert, Denise Brigitte; Justus Liebig University Giessen (My University, 2018)
Regrowth and growth dynamics of crop plants after mowing and cutting influence the profitability of their use in agriculture and therefore their improvement are important economic target traits for plant breeding. However, little is known about regrowth dynamics and their underlying molecular mechanisms, especially in non-model organisms. In this study I show how molecular genetic analysis can provide explanations to unravel documented regrowth pattern of Trifolium pratense (red clover). During an introductory experiment, T. pratense was shown to exhibit specific morphogenetic changes in response to cutting, including altering leaf morphology and plant architecture. Moreover it was demonstrated that red clover plants exhibit two different growth strategies resulting in high and low performing plants, and cutting acts as an artificial trigger. This can initiate a second growth phase even in low performing plants and contributes to yield increase. Transcriptome analysis of 32 T. pratense plants, including two treatments (mown/not mown) and two conditions (field/greenhouse), was made, to investigate the molecular mechanisms of the observed phenotypic changes. This resulted in 12 high quality transcriptomes. In total the draft assembly consists of 44,643 contigs with an N50 value of 1,656 (bp). A reference based annotation of the T. pratense genome revealed 24073 known and 4051 newly identified plant specific transcripts. The identification of functional groups within the differentially expressed contigs revealed site specific structures within the transcriptomes, indicating that the plants grown in the greenhouse are less influenced by environmental stress and therefore show a stronger expression of genes related to regrowth. The results of the digital gene expression allowed the identification of candidate genes involved in the plant response during regrowth and could be partially validated via qRT-PCR. In total 14 candidate genes have been selected for further functional analysis including qRT-PCR and t-DNA insertion mutant analysis in the model plant A. thaliana. The phenotypic monitoring of these A. thaliana t-DNA mutant lines displayed gene specific individual growth and regrowth patterns. The results of the phenotypic monitoring, the transcriptome analysis, and the functional analysis, were combined in working models that hypothesizes how regrowth takes place. Therefore T. pratense plants potentially overcome the first stress response after cutting on a molecular level by reprogramming the pathways involved in immune response from inhibiting growth, to promoting growth. In addition further growth activating pathways are activated during regrowth, involving the phytohormone gibberellin. Rapid regrowth and leaf morphology changes could be achieved by expression of genes involved in cell wall modifications. The study provides a good basement to identify the mechanisms involved in regrowth and shift in growth strategies.

Das Nachwachsen, sowie die Wachstumsdynamik von Futterpflanzen nach der Mahd entscheiden darüber wie profitabel deren Anbau ist. Die Verbesserung dieser Eigenschaften stellt daher ein wichtiges ökonomisches Ziel in der Pflanzenzucht dar. Dennoch ist bis heute wenig über Nachwuchsdynamik und der zugrunde liegenden molekularen Mechanismen bekannt, insbesondere in Nicht-Modell Organismen. In dieser Studie zeige ich wie molekular genetische Analysen dabei helfen Erklärungen für die Prozesse des Nachwachsens bei Trifolium pratense (Rotklee) zu finden. Während eines einleitenden Experiments wurde gezeigt, dass T. pratense spezifische morphogenetische Veränderungen als Reaktion auf die Mahd zeigt, wozu Veränderungen der Blatt Morphologie und Pflanzen Architektur gehören. Desweiteren wurde gezeigt, dass Rotklee zwei unterschiedliche Wuchsstrategien hat: viel und wenig produzierende Pflanzen. Die Mahd stellt einen künstlichen Auslöser für eine zweite Wachstumsphase dar, auch in den wenig produzierenden Pflanzen, wodurch ein Zugewinn an Biomasse entsteht. Um die beobachteten morphologischen Veränderungen molekular genetisch zu erklären wurde eine Transkriptomanalyse von insgesamt 32 T. pratense Pflanzen (gemäht/nicht gemäht; Feld/Gewächshaus) durchgeführt. Daraus resultierten 12 Transkriptome, deren vorläufige Rekonstruktion insgesamt 44.643 contigs umfasste, mit einem N50 Wert von 1.656 (bp). Die referenzbasierten Annotation mit dem T. pratense Genom, identifizierte 24.073 bekannte und 4051 neue pflanzenspezifische Transkripte. Die Einteilung der Transkripte in funktionale Gruppen zeigte standortspezifische Muster, laut denen Gewächshauspflanzen weniger von umweltbedingten Einflüssen gestresst werden und eine stärkere Expression von Genen des Nachwuchsprozess aufzeigen. Durch die Analyse der digitalen Genexpression wurden Kandidatengene ausgewählt, die in den Nachwuchsprozess involviert sind. Dies wurde teilweise durch qRT-PCR Analysen validiert. Insgesamt wurden 14 Kandidatengene für weitere funktionale Studien ausgewählt, die sowohl qRT-PCR als auch t-DNA Mutanten Analysen in A. thaliana umfassten. Die phänotypische Untersuchung der t-DNA Mutanten zeigte genspezifische Wuchs- und Nachwuchsmuster. Die Ergebnisse der phänotypischen Untersuchung, der Transkriptomanalyse und der funktionellen Analysen wurden miteinander kombiniert um Arbeitsmodelle zu entwerfen die als Erklärung des Nachwuchsprozesses bei T. pratense dienen. Hierbei entstand die Hypothese, dass Rotklee, Mechanismen der meist wachstumshemmenden Immunantwort in wachstumsfördernde umprogrammieren. Zusätzlich werden weitere wachstumsfördernde Mechanismen aktiviert welche das Phytohormon Gibberellin involvieren. Das schnelle Nachwachsen und die Veränderungen der Blattmorphologie könnte durch die Aktivierung von Genen für Zellwandveränderungen ermöglicht werden. Die hier vorliegende Studie bietet eine gute Grundlage um Mechanismen die in das Nachwachsen und in den Wechsel der Wuchsstrategien involviert sind zu identifizieren.
Vergleichende Transkriptom Analyse und phänotypisches Monitoring von Trifolium pratense L. (Fabaceae) unter Landnutzungsbedinungen
Keywords: Trifolium pratense; Rotklee; Transkriptom; phänotypisches Monitoring; Trifolium pratense; red clover; transcriptome; phenotypic monitoring; ddc:580